A Comparative Study of Corporate Criminal Liability Systems in Indonesia and the United States - Ismaidar Ismaidar; Azhar AR; Servasius Edwin Telaumbanua; Rudi Salam Tarigan; Ansori Maulana; Restika Ndruru; Zeno Eronu Zalukhu; Lasma Sinambela; Haris Putra Utama Limbong; Elisabeth Saragih; Robby Yusuf S Sembiring; Mus Mulyadi; Zahrana Syavica; Tengku Muhammad Reza Fikri Dharmawan; Muhammad Faiz Hadi; Ibrahim Ibrahim; Erwin Efendi Rangkuti; T. Ikhsan Ansyari Husny; Netty br Siahaan; Andi Gultom; Yoldy Israq; Putriani Nduru; Yulia Christy Shintara Aruan; Christine Natalia Pangaribuan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Corporate criminal liability has become a pivotal issue in modern criminal law, particularly in response to the increasing prevalence of crimes committed by legal entities. This article provides a comparative analysis of the corporate criminal liability systems in Indonesia and the United States, focusing on the legal foundations, models of liability, and enforcement practices. The United States adopts the principle of vicarious liability, allowing corporations to be held accountable for the acts of their employees performed within the scope of employment. In contrast, Indonesia employs a more fragmented approach through sectoral laws, without a unified criminal liability doctrine for corporations. The study reveals that while Indonesia has begun to recognize corporate liability, it still faces significant challenges in legal harmonization and effective enforcement. This comparison aims to contribute to the development of a more comprehensive and adaptive corporate criminal liability system in Indonesia, in line with international best practices.